Proposições para o fortalecimento da educação ambiental na área de influência da UHE Tucuruí: sob o olhar da percepção ambiental de docentes do ensino fundamental - TEIXEIRA, Thaise Daniele Paixão (Universidade Federal do Pará, 2024)
The study examines environmental perception considering the construction of the Tucuruí Hydroelectric Power Plant, which led to a series of spatial, social, and environmental changes within the project's affected area. This transformation altered the human-nature relationship and individuals' perception of their environment. The research aims to contribute to the strengthening of public policies, particularly within the framework of measures designed to mitigate the impacts of hydroelectric plants. This will be achieved through an analysis of the Environmental Perception of public school teachers involved in the environmental education program of the Tucuruí Hydroelectric Power Plant within its scope of influence. The study is conducted across six schools situated in the municipalities of Tucuruí and Breu Branco, involving a total of 60 teachers and 6 administrators as participants. Data collection involved semi-structured interviews with school administrators and open-ended questionnaires directed to teachers. Quantitative data were systematically processed and organized, with results depicted in graphs. Qualitative data were analyzed using content analysis, aided by the IRaMuTeQ Software. The outcomes of this investigation revealed that the majority of participants possessed knowledge about the educational initiatives aimed at raising awareness about the Environmental Education Program (AEP) of the Tucuruí HPP. However, despite acknowledging the program's limitations, most teachers believe that the AEP contributes to mitigating environmental degradation in the vicinity of the Tucuruí HPP. Nevertheless, it is imperative to critically examine the socio-economic and cultural context of the communities, identifying potential issues before implementing activities. This entails considering the diverse environments and historical ties of those affected by the project. Consequently, investing in and intensifying the program's presence within the school environment becomes essential. This underscores the need for enhanced training and program adjustments that foster meaningful learning and the development of environmentally conscious citizens.